Penggunaan E-Modul Praktikum Biologi di SMAN 16 untuk Meningkatkan Hasil Belajar Siswa - Ramadansur, Rahmat; Sembiring, Al Khudri; Qomariah, Nurul; Ardiani, Rosa (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2025)
This study aims to analyze the effectiveness of the use of the Biology practicum e-module at SMAN 16 in improving student learning outcomes. With the rapid development of information technology, e-modules are expected to facilitate the learning process, especially in practicum materials that are often hampered by limited equipment and time. This study adopted an experimental method with a pretest-posttest control group design. The study sample involved eleventh-grade students who were divided into two groups: an experimental group that utilized the e-module and a control group that used a conventional practicum module. Data were collected through learning outcome tests (before and after the practicum) and observations of the learning process. Data analysis was conducted using a t-test to compare the learning outcomes of the two groups. The results showed that the use of the Biology practicum e-module significantly improved student learning outcomes compared to the conventional module. The e-module was proven to provide easy access, increase interactivity, and deepen students' understanding of the practicum material. Student responses to the e-module were also very positive, with an overall feasibility rate reaching 91.76%, where the ease of use aspect was highly appreciated. Thus, this e-module can be used as an effective learning alternative to support Biology subjects in secondary schools, while also encouraging student independence and motivation in the digital age.